Systematic Literature Review: Karakteristik UI/UX Efektif untuk Efisiensi Sistem Informasi UMKM - Dhewanty, Civica Moehaimin; Ayu, Putu Desiana Wulaning; Apriyanthi, Ni Putu Eka (Prodi Sistem Informasi Universitas Dharma Andalas, 2026)
Technological and internet development in Indonesia, with 229.42 million users in 2025, presents a significant opportunity for Micro, Small, and Medium Enterprises (MSMEs) to market their products online. However, the low adoption rate of information systems by MSMEs, particularly concerning effective User Interface/User Experience (UI/UX), can directly impact business success and customer interest in making purchases. The main problem addressed in this study is identifying the most effective UI/UX characteristics for supporting the efficiency of online selling media for MSMEs. This research aims to identify the most crucial UI/UX characteristics that strongly influence and can be used as a reference for developing more efficient MSME online sales media, using a Systematic Literature Review (SLR) approach. The SLR method, following Kitchenham's stages, was employed to analyze 30 articles published between 2021 and 2025, which focused on UI/UX for MSME online selling media, used Design Thinking or UCD approaches, and included System Usability Scale (SUS) evaluation. The analysis of the top-performing articles (based on SUS scores) revealed five dominant UI/UX characteristics: simple and intuitive navigation, visual interface consistency, cross-device responsiveness, high accessibility, and interactivity and personalization. While UCD tends to yield the highest usability scores (up to SUS 94) due to its focus on real user needs, Design Thinking is also consistent in producing